EDUKASI BULLYING PADA SISWA/I SDN 29 PEBAYAN PENGGALANGAN KECAMATAN PADANG SELATAN KOTA PADANG - Suci Maisyarah Nasution; Putri Rahmadani; Dinda Aisyah Salsabila; Dhea Amelia; Laura Prissa Utama; Nadia Intan (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Bullying behavior is an aggressive attitude of a person or group that can hurt others physically and non-physically repeatedly. A person's goal in bullying is to show others that they are tough, strong and great. In Indonesia, in 2015, UNICEF reported an increase in violence against children and adolescents, with 26% of physical violence committed by parents and caregivers, 40% of physical bullying and 50% of incidents in schools. Socialization activities were carried out to partners, namely Public Alementary School 29 Pebayan Penggalangan, Padang Selatan Sub- District, who explained that the bullying case still did not exist, but also for socialization and education had never been carried out in the school environment. The purpose of this activity is to provide education about bullying to students so that there are no victims or perpetrators of bullying in the school environment. The method used in this activity is lecture. The purpose of this activity is to provide education about bullying to students so that there are no victims or perpetrators of bullying in the school environment. The method used in this activity is lecture. This activity began with filling out a pretest and then ending with filling out a post-test to measure students' knowledge about bullying. The questions given are sourced from the explanations delivered during the socialization. The results of this activity were that the results of the pretest were obtained by more than half of the students (70%) knew about bullying and the results of the post-test showed an increase in knowledge of 95%. The conclusion is that there is an increase in student discipline after receiving education about this bullying. This activity is expected so that students do not normalize bullying attitudes at school.